2020
DOI: 10.3390/ijms21218007
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Parkin Results in Altered Muscle Stem Cell Differentiation during Regeneration

Abstract: The high capacity of the skeletal muscle to regenerate is due to the presence of muscle stem cells (MuSCs, or satellite cells). The E3 ubiquitin ligase Parkin is a key regulator of mitophagy and is recruited to mitochondria during differentiation of mouse myoblast cell line. However, the function of mitophagy during regeneration has not been investigated in vivo. Here, we have utilized Parkin deficient (Parkin–/–) mice to investigate the role of Parkin in skeletal muscle regeneration. We found a persistent def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In addition to the importance of metabolic reprogramming, other mitochondrial processes are implicated in optimal SC function. For instance, competent mitophagy has been shown to be necessary for normal SC activity in a study that examined Parkin null mice (Esteca et al, 2020). Parkin is an E3 ubiquitin ligase that is essential for regulation of mitophagy.…”
Section: Satellite Cell Mitochondrial Function and Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the importance of metabolic reprogramming, other mitochondrial processes are implicated in optimal SC function. For instance, competent mitophagy has been shown to be necessary for normal SC activity in a study that examined Parkin null mice (Esteca et al, 2020). Parkin is an E3 ubiquitin ligase that is essential for regulation of mitophagy.…”
Section: Satellite Cell Mitochondrial Function and Vitamin Dmentioning
confidence: 99%
“…Parkin knockout resulted in increased SC proliferation and impaired differentiation in mouse skeletal muscle following injury with cardiotoxin. These changes in SC activity were accompanied by delayed skeletal muscle fiber repair and smaller muscle fibers during regeneration (Esteca et al, 2020).…”
Section: Satellite Cell Mitochondrial Function and Vitamin Dmentioning
confidence: 99%
“…Thus, it is reasonable to speculate that Parkin reduction is not the only mechanism for MuRF‐1 expression during CS exposure and that other possibilities should be elucidated. Third, a recent paper showed that Parkin‐mediated mitophagy might play a role in regulating muscle stem cell differentiation 43 . The results of our experiment demonstrated that CSE (2%) exposure induced a significantly lower expression levels of myogenin, a key transcription factor for myotube differentiation, in myoblasts, which was further reduced in CSE‐treated Parkin KD myoblasts (data not shown).…”
Section: Discussionmentioning
confidence: 46%
“…Third, a recent paper showed that Parkin‐mediated mitophagy might play a role in regulating muscle stem cell differentiation. 43 The results of our experiment demonstrated that CSE (2%) exposure induced a significantly lower expression levels of myogenin, a key transcription factor for myotube differentiation, in myoblasts, which was further reduced in CSE‐treated Parkin KD myoblasts (data not shown). Hence, it is likely that not only increased degradation of muscle proteins but also reduced muscle regeneration may be involved in the development of COPD‐related sarcopenia associated with insufficient Parkin‐mediated mitophagy, which should be examined in future studies.…”
Section: Discussionmentioning
confidence: 67%
“…Mitochondrial function is critical for muscle repair after injury considering its role in modulating satellite cells activity [61], as demonstrated by reduced oxidative capacity in quiescent satellite cells [62]. Moreover, modulation of mitochondrial mitophagy seems to be necessary to satellite cell function, as demonstrated in mouse models knock-out for Parkin, an E3 ubiquitin ligase [63], that showed reduced differentiation of satellite cells and, consequently, poor muscle regeneration. These data confirm that mitophagy favors the increase and maintenance of the satellite cells pool.…”
Section: Vitamin D and Sport-related Muscle Injury: From Biology To Clinical Practicementioning
confidence: 99%